Eating disorders - anorexia as an interdisciplinary problem - Elżbieta Sowińska-Przepiera; Martyna Patalong-Wójcik; Elżbieta Andrysiak-Mamos; Dariusz Starzyński; Marek Przestalski; Anhelli Syrenicz (Kazimierz Wielki University, 2019)
Eating disorders are a significant medical and social problem. The most commonly diagnosed eating disorders include anorexia nervosa (AN) and bulimia nervosa, currently classified as behavioral disorders. Anorexia nervosa is a disease consisting in deliberate weight loss and disturbed its image and dysmorphophobia, often coexisting with symptoms of depression and social withdrawal. Understanding the problem of anorexia is not just about food or body mass. Underlying disorders include, among others: emotional problems, the need to define your own identity, a negative image of yourself. AN in women in the general population occurs at a frequency of 0.5-1%, in men 0.05-0.1%, in Poland it ranges from 0.8% -1,8% of the population of girls